Inovasi Pembelajaran Bahasa Indonesia dengan Model Sinektik dan Media Kartu Balon Ceria untuk Mengembangkan Keterampilan Menulis dan Penalaran Kritis Murid SD Kelas 1 - Nur Aini, Putri Intan; Purwanti, Panca Dewi (YASIN, 2025)
Writing is a fundamental skill that primary school students need to master, particularly during the initial literacy phase in Grade 1; however, in practice many students still face challenges because the instructional media used are not sufficiently engaging, relevant, or supportive of their learning needs. This study aims to describe the development process and use of the Kartu Balon Ceria (Cheerful Balloon Cards) medium as a means to improve beginning writing skills and critical reasoning among first-grade students. The medium was designed to promote cheerful, meaningful, and mindful learning through colourful balloon-shaped displays containing letters, words, and images closely related to students’ everyday experiences. The development stages included concept formulation, visual design, selection of colours and symbols that are easy to understand, and the design of game-based activities that support early literacy skills. In its implementation, students were engaged in activities such as tracing letters, arranging letters into words, sequencing words according to pictures, and writing their own names using correct spelling, thereby enhancing phonemic awareness, facilitating fine motor development, and fostering critical reasoning by linking symbols, visuals, and meaning. The findings show that the Kartu Balon Ceria medium increases student participation, strengthens early-stage writing ability, and stimulates critical reasoning through exploratory activities and interactive games. Accordingly, this medium can be regarded as an effective and feasible innovation for use in Indonesian language instruction in lower grades to support the reinforcement of early literacy in an enjoyable and meaningful way.